The application of U-isotopes to assess weathering in contrasted soil-water regime in Brazil - Rosolen, Vania [UNESP]; Bueno, Guilherme Taitson; Bonotto, Daniel Marcos [UNESP] (Elsevier, 2018)
This paper presents the use of U-series radionuclides 238U and 234U to evaluate the biogeochemical disequilibrium in soil cover under a contrasted soil-water regime. The approach was applied in three profiles located in distinct topographical positions, from upslope ferralitic to downslope hydromorphic domain. The U fractionation data was obtained in the samples representing the saprolite and the superficial and subsuperficial soil horizons. The results showed a significant and positive correlation between U and the Total Organic Carbon (TOC). Soil organic matter has accumulated in soil due to hydromorphy. There is no evidence of positive correlation between U and Fe, as expected in lateritic soils. The advance of the hydromorphy on Ferralsol changes the weathering rates, and the ages of weathering are discussed as a function of the advance of waterlogged soil conditions from downslope. Also, the bioturbation could represent the other factor responsible to construct a more recent soil horizon.
Keywords: Dating; Hydromorphy; Lateritic soil; Marilia formation; Uranium isotopes